Speciation of Soil Phosphorus Assessed by XANES Spectroscopy at Different Spatial Scales. Issue 6 (1st November 2017) - Hesterberg, Dean; McNulty, Ian; Thieme, Juergen
Abstract : Precise management of soil phosphorus (P) to meet competing demands of agriculture and environmental protection can benefit from more comprehensive characterization of P speciation in soils. Our objectives were to provide spatial context for spectroscopic analyses of soil P speciation in relation to molecular‐scale species and landscape‐scale management of P, and to compare soil P‐species diversity from spectroscopic measurements at submicron and millimeter scales. The spatial range of ∼26 orders of magnitude between atomic and field scales presents a challenge to upscaling and downscaling information from spectroscopic analyses of soils. Scanning fluorescence X‐ray microscopy images of a 50‐μm × 45‐μm area of an organic soil sample showed heterogeneous distributions of P, Al, and Si. Microscale X‐ray absorption near edge structure (μ‐XANES) spectra collected at the P K‐edge from 12 spots on the soil sample exhibited diverse features that indicated variations in highly localized P speciation. Linear combination fitting analysis of the μ‐XANES spectra included various proportions of three standards that appeared in fits for most spots and five standards that appeared in fits for one spot each. The fit to a bulk‐soil spectrum was dominated by two of the common standards in the μ‐XANES fits, and a fit to the sum of μ‐XANES spectra included four of the standards. These results illustrate a gain in P species sensitivity from spatially resolved XANES analysis. Integrating spectroscopic analyses from multiple scales determines soil P species diversity and will ultimately help connect speciation to the chemical reactivity and mobility of P in soils. Core Ideas: Diverse molecular‐scale species of phosphorus occur in a soil. XANES analysis at different scales connects speciation across scales. Microscale XANES spectroscopy analysis improves detection of minor P species. Bulk‐sample XANES spectroscopy analyzes major P species in a representative volume.